Education, Information, and Smoking Decisions : Evidence from Smoking Histories in the United States, 1940-2000 - de Walque, Damien (2012)
This paper tests the hypothesis that education improves health and increases life expectancy. The analysis of smoking histories shows that after 1950, when information about the dangers of tobacco started to diffuse, the prevalence of smoking declined earlier and most dramatically for college graduates. I construct panels based on smoking histories in an attempt to isolate the causal effect of smoking from the influence of time-invariant unobservable characteristics. The results suggest that, at least among women, college education has a negative effect on smoking prevalence and that more educated individuals responded faster to the diffusion of information on the dangers of smoking.